ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH PROVINSI DI INDONESIA TAHUN ANGGARAN 2013-2015 - Intan Cristiana, 13.05.52.0236; Maryono, Maryono (Students' Journal of Accounting and Banking, 2017)
This research aims to investigate and analyze factors that influence provincial government disclosure fiscal years 2013-2015. Independent variables in this research are the level of dependence, realized of revenue, total asset, population, number of units under Provincial (SKPD), number of audit findings and level of financial irregularities. The results showed that realized of revenue and number of units under Provincial (SKPD) have positive and significant influence on the disclosure level of provincial government financial statements. While total asset have negative effect and significant influence on the disclosure level of provincial government financial statements. However, the level of dependence, population, number of audit findings and level of financial irregularities do not significantly influence the disclosure level of provincial government financial statements.Keywords: Influence Provincial Government Disclosure, BPK Audit Results, Government Accounting Standard, Good Public Government